(untitled) (Fair Play, 2025)
This study aims to analyze the influence of fanatic behavior on students' academic performance, specifically among members of the Persis Solo supporter group at SMA Batik 2 Surakarta. A qualitative descriptive approach was used, with data collected through questionnaires, interviews, and documentation. The research subjects consisted of 30 students who were members of the supporter community. The results show that 40% of the students exhibited a high level of fanaticism; However, this does not have a negative impact on their academic performance. On the contrary, fanaticism serves as a motivational factor that drives students' enthusiasm for learning. The main supporting factors include effective time management, internal motivation, and support from the social environment. Well-managed fanaticism can become a positive force in students' academic life.